2005
DOI: 10.1038/sj.cr.7290303
|View full text |Cite
|
Sign up to set email alerts
|

Differential regulation of survivin by p53 contributes to cell cycle dependent apoptosis

Abstract: Recent studies indicate that cell-cycle checkpoints are tightly correlated with the regulation of apoptosis, in which p53 plays an important role. Our present works show that the expression of E6/E7 oncogenes of human papillomavirus in HeLa cells is inhibited in the presence of anti-tumor reagent tripchlorolide (TC), which results in the up-regulation of p53 in HeLa cells. Interestingly, under the same TC-treatment, the cells at the early S-phase are more susceptible to apoptosis than those at the middle S-pha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 42 publications
1
12
0
Order By: Relevance
“…Several reports showed that TC inhibited the proliferation of peripheral blood mononuclear cells [26], mesangial cells [27] and spermatocytes [28]. It was also reported that TC could induce apoptosis of cells in both p53-dependent and p53-independent manner [29,30]. Moreover, our group showed that TC caused DNA damage in CHO cells and induced the degradation of c-Myc protein [31].…”
Section: Introductionmentioning
confidence: 59%
See 4 more Smart Citations
“…Several reports showed that TC inhibited the proliferation of peripheral blood mononuclear cells [26], mesangial cells [27] and spermatocytes [28]. It was also reported that TC could induce apoptosis of cells in both p53-dependent and p53-independent manner [29,30]. Moreover, our group showed that TC caused DNA damage in CHO cells and induced the degradation of c-Myc protein [31].…”
Section: Introductionmentioning
confidence: 59%
“…6A and 6D). To address whether the activated p53 involved in the degradation of pRB in the TC treated AGS cells, an AGS-derivative cell line, AER, containing the p53 dominant-negative was constructed (see Materials and methods) [30]. When the cells were administrated with 20 ng/ml TC for the indicated times, there was the pRB reduction of the TC-treated AER cells in a time-dependent manner (Fig.…”
Section: Tc-induced Prb Degradation Of Ags Cells Was P53 Independentmentioning
confidence: 99%
See 3 more Smart Citations